'Aur-Auran' as a Language of Digital Cultural Expression in Live Streaming: An Analysis of Its Connotation Meaning and Impact among Virtual Audiences - Chiquita Dewi Nada Nisrina; Kirana Aridhani Wahidah; Fatin Kusuma Anggraini; Elana Deswita; Aprilia; Lungit Kusuma Ningrum (Journal of Applied Linguistics, 2026)
This research aims to understand the connotative meaning in the lyrics of the song "Aur-Auran" by Windah Basudara, examine its impact on the virtual audience, and identify the factors influencing the song’s popularity. Using a descriptive qualitative approach, data were collected through lyric observation, listening, and online questionnaires. The findings show that the song carries positive connotations, such as moral advice and motivation, though some expressions contain negative nuances that may be less suitable for younger audiences. The impact varies: 29% of respondents feel motivated to improve themselves, 20% enjoy the humor, and 12% criticize certain inappropriate terms. The song’s popularity is driven by its creative, spontaneous, and interactive delivery. This study contributes to the understanding of how digital music content conveys connotative meaning, influences audiences in virtual spaces, and shapes cultural interaction in the digital era. Keywords : Meaning of the song; semantic analysis; windah basudara